2019
DOI: 10.1073/pnas.1907181116
|View full text |Cite
|
Sign up to set email alerts
|

Fine control of aerenchyma and lateral root development through AUX/IAA- and ARF-dependent auxin signaling

Abstract: Lateral roots (LRs) are derived from a parental root and contribute to water and nutrient uptake from the soil. Auxin/indole-3-acetic acid protein (AUX/IAA; IAA) and auxin response factor (ARF)-mediated signaling are essential for LR formation. Lysigenous aerenchyma, a gas space created by cortical cell death, aids internal oxygen transport within plants. Rice (Oryza sativa) forms lysigenous aerenchyma constitutively under aerobic conditions and increases its formation under oxygen-deficient conditions; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 40 publications
4
110
0
Order By: Relevance
“…As RSAvis3D employs intensity changes to enhance root segments, root-to-soil contrast is an important factor for efficient root isolation. Rice roots produce constitutive aerenchyma under aerobic conditions, but most field crops do not [46,47], suggesting that rice tends to show higher contrast between its roots and the surrounding soil than other crops that do not produce constitutive aerenchyma. We need to consider the soil substrate that is available when RSAvis3D is applied to other crops.…”
Section: Discussionmentioning
confidence: 99%
“…As RSAvis3D employs intensity changes to enhance root segments, root-to-soil contrast is an important factor for efficient root isolation. Rice roots produce constitutive aerenchyma under aerobic conditions, but most field crops do not [46,47], suggesting that rice tends to show higher contrast between its roots and the surrounding soil than other crops that do not produce constitutive aerenchyma. We need to consider the soil substrate that is available when RSAvis3D is applied to other crops.…”
Section: Discussionmentioning
confidence: 99%
“…As RSAvis3D employs intensity changes to enhance root segments, root-to-soil contrast is an important factor for efficient root isolation. Rice roots produce constitutive aerenchyma under aerobic conditions, but most field crops do not [47,48], suggesting that rice tends to show higher contrast between its roots and the surrounding soil than other crops that do not produce constitutive aerenchyma. We need to consider the soil substrate that is available when RSAvis3D is applied to other crops.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IAA14, IAA9, IAA1, IAA12, and other members are all involved in the growth and development of roots in different plants (Fukaki et al, 2002;Smet and Beeckman, 2010;Sha et al, 2015). Recent studies have found that A. thaliana mutant iaa13 reduced lateral roots, which affected root configuration (Takaki et al, 2019). In addition, auxin output vectors composed of PIN family proteins, such as PIN1, PIN2, PIN3, PIN4, PIN5, PIN6, PIN7, and PIN8, are distributed in different tissues, where they regulate auxin synthesis and affect plant growth and development (Gälweiler et al, 1998;Friml and Palme, 2002;Blilou et al, 2005;Dubrovsky, 2008;Müller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%